Monopoli dalam Perspektif Ekonomi Islam - Anriza Witi Nasution; Rahmad Azahar Siregar; Isnaini Harahap (Universitas Batanghari Jambi, 2022)
Monopoly is one of a form of market failure. Monopoly have a positive or negative impact. The positive impact of monopoly will only be obtained by greedy producers in the form of profit maximization. Meanwhile, the negative impact on small businesses and consumers can make a destruction of society. Small businesses will not be able to survive in a monopoly market, while consumers will experience a scarcity of goods and services due to monopoly. The impact of monopoly, which is a derivative of the capitalist economic system, is felt by consumers, so the emergence of an Islamic economy provides new hope for economics. This study aims to describe the Islamic view of monopoly. This type of research is library research using descriptive qualitative methods. Data were obtained from various secondary data sources related to monopoly. The results of this study indicate that in Islamic terminology there is no concrete term monopoly, but monopoly is almost similar to ikhtikar. Basically, monopoly that shows indications of ikhtikar is a prohibited category of monopoly, although there are still differences of opinion among mujtahid regarding the law of ikhtikar, whether it is haram or makruh. The mujtahid then gave the conditions for ikhtikar which were prohibited based on the hadith about ikhtikar. The Islamic government led by the Prophet Muhammad also implemented a monopoly, but it was not a monopoly that was categorized as ikhtikar. The monopoly applied by the Prophet Muhammad is the control of the state over state assets that contain the livelihood of many people